Eklektik filosofis, teknis, dan psikologis bermain biola dalam pengembangan pembelajaran musik di Indonesia - Fu'adi, Fu'adi; Walidaini, Birul; Agustianto, Agustianto; Sritanto, Sritanto (Imaji: Jurnal Seni dan Pendidikan Seni, 2023)
In learning the violin, there are various kinds of challenges and obstacles, both technical and non-technical. Strong motivation is needed, supported by appropriate learning methods so that students can develop into capable violinists. This article outlines the philosophical, technical, and psychological aspects of violin learning by world-class violin pedagogues, which are then analyzed in an eclectic manner in order to obtain new approaches that can be applied to develop violin learning in Indonesia. The literature review method is used to select important aspects used in violin learning. The research results show important points of philosophical study in learning the violin include philosophy in starting to learn the violin, mental approach, emotional aesthetics, and talent in music. Technical and psychological studies include body position in playing the violin, sound production, intonation, vibrato, legato, musical nuances, psychological musicians, and the repertoire played. It can be interpreted that these selected and analyzed philosophical, technical, and psychological values of how to play the violin can become the basis for understanding and efforts to build students' capabilities in playing the violin in a comprehensive manner, in accordance with the Indonesian cultural background. Keywords: Eclectic, philosophy, violin technique, musical learning